Panggilan dan Pemilihan Allah dalam Konstruksi Soteriologis Petrus: Refleksi Teologis 2 Petrus 1:3-11 - Tjandra, David S. (Sekolah Tinggi Alkitab Jember, 2022)
The assumption that salvation has been completed is very unbiblical because humans must complete God's work of salvation that has been given. Salvation for humans who have fallen into sin and have a sinful nature is not enough just with the forgiveness of sins; they must leave their sinful nature. The Holy Spirit was sent to help a man become holy by changing his nature throughout life from sinful to divine. Using a qualitative method with a literature study approach and text analysis, it can be concluded that Jesus' redemption for all people has been completed, but for believers, there is a demand to do what He taught. Because of Christian salvation, Christianity does not tolerate sin; Christianity is not a teaching that allows sinners to enter heaven because of grace. The salvation that is understood to have been completed or perfect is